Could mesenchymal stromal cells have a role in childhood autoimmune diseases?. (October 2013) - Pesmatzoglou, Margarita; Dimitriou, Helen; Stiakaki, Eftichia
Abstract : Mesenchymal stromal cells (MSCs) comprise a promising source for cellular therapy due to their ability to be readily isolated from various tissues and expand ex vivo. A unique property of these cells is the modulation of immune responses, making them attractive candidates for the treatment of autoimmune diseases. Recently, several clinical trials, mainly in adults, suggest the use of MSCs for therapy of refractory autoimmune diseases. There are a very limited number of reports in the literature addressing the cellular therapy options for pediatric patients with autoimmune diseases refractory to standard therapy. This review discusses the possible mechanisms underlying the immunosuppressive effects of MSCs on almost all cell types, and also the recent advances in cellular therapy of autoimmune diseases using MSCs as modulators of immune response, especially in children.